Physicochemical and Microbiological Assessment of Fresh and Frozen Fish Marketed in the Coastal Area of Togo - Sefako Mireille Agonsa; Ekpetsi Chantal Bouka; Achite Antony Mensah; Abdou-Hakimou Koura-Ketchim; Povi Lawson-Evi; Kwashie Eklu-Gadegbeku (European Scientific Journal, ESJ, 2026)
In Togo, seafood consumption is based on local fishing and imports. Local and imported fish pass through various distribution channels and undergo several post-fishing handling processes, which can impact their physicochemical and microbiological qualities. To assess the physicochemical and microbiological qualities of fresh and frozen fish subjected to various handling practices, samples were collected from fishermen, wholesalers, importers and fish shops, and then analyzed. The sampling used a mixed approach, combining a reasoned non-probabilistic selection of collection sites with a random probabilistic selection of actors present at each site during sample collection. Thus, 42 actors were sampled at targeted landing and commercialization sites for fresh and frozen fish, selected based on their importance. Based on defined criteria, 22 composite samples of fresh and frozen fish were formed and submitted for analysis. Freshness and Total Volatile Basic Nitrogen (TVBN) were assessed according to European Regulations, pH by the potentiometric method, and microbiological analysis according to AFNOR's analytical methods. The results showed that fish from beach fishermen and importers had the highest freshness index (I=3), followed by seining fishermen (I=2.4), fish shops (I=2.2), and wholesalers (I=1.8). The pH ranged from 5.72 (importers) to 6.96 (wholesalers), and the Total Volatile Basic Nitrogen (TVBN) ranged from 5.40 mg/100g (importers) to 112.62 mg/100g (fish shops). 81.82% of the samples had TVBN levels below the threshold of 25 mg/100g. Fish from importers were of satisfactory microbiological quality, those from fishermen and fish shops were of acceptable quality, and those from wholesalers were of unsatisfactory quality. Salmonella was not detected in any sample. This study revealed that fish quality varies depending on the different actors involved and therefore different practices in the commercialization chain. Frozen fish upon entry into the country were of better quality, followed by locally freshly caught fish, fish marketed by fish shops and finally by fish from wholesalers. Our results highlight the need to strengthen awareness campaigns and training on good hygiene, fishing, and commercialization practices, especially for local fishing stakeholders.